Crystalline phases and optical properties of titanium dioxide films deposited on glass substrates by microwave method - Promnopas W. (2017)
© 2016 Elsevier B.V. Anatase films were deposited on glass substrates by 180, 300, 450 and 500 W microwave for 1.5 min. Upon calcination the 450 and 500 W films at 450 °C for 1 h, additional rutile phase was detected by X-ray diffraction (XRD). Scanning electron microscopy (SEM) and atomic force microscopy (AFM) analyses revealed morphologies of the films which were composed of a number of nanoparticles orientated in different directions with the lowest roughness for the film synthesized by 450 W microwave combined with the high temperature calcination. Band gaps of the films without calcination determined by UV–visible spectroscopy were 3.30–3.35 eV and were considerably decreased to 2.92–3.20 eV by the high temperature calcination.